A systematic review on the fourth industrial revolution: African basic schools' readiness - Omotayo Adewale Awodiji; Ancia Katjiteo (Jurnal Bidang Pendidikan Dasar, 2023)
This systematic review's primary goal is to determine how prepared African basic schools are for implementing 4IR tools and how well-versed in 4IR the teachers in African basic schools are. A systematic review approach was adopted. Data base such as Johannesburg e-library, ProQuest, and Google scholar was used to search for relevant study used.  It was determined that the findings were valid and rigourous through the use of PRISMA. Out 106,859 resource generated, the review included 18 studies that met the inclusion and exclusion criteria. The study highlights the necessity for African basic schools to enhance their preparedness for the Fourth Industrial Revolution (4IR). Funding is crucial to provide the necessary 4IR infrastructures, suggesting the allocation of resources by the African government for procurement and deployment of 4IR tools. Additionally, implementing a program to train teachers and school leaders in 4IR technologies is recommended to enhance their capabilities.